2004
DOI: 10.1093/ajcn/80.4.855
|View full text |Cite
|
Sign up to set email alerts
|

Dietary cholesterol does not increase biomarkers for chronic disease in a pediatric population from northern Mexico

Abstract: Intake of 2 eggs/d results in the maintenance of LDL:HDL and in the generation of a less atherogenic LDL in this population of Mexican children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
68
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(72 citation statements)
references
References 40 publications
3
68
1
Order By: Relevance
“…Although data on dietary habits and physical activity were not collected. Results from others studies [36][37][38] in urban locations of the same region showed that children consumed a hypercaloric diet, with adequate quantities of protein and fiber but excessive amounts of simple carbohydrates and saturated fat and a low quantity of polyunsaturated fat. Those studies also showed that most of the children were sedentary [36,38].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although data on dietary habits and physical activity were not collected. Results from others studies [36][37][38] in urban locations of the same region showed that children consumed a hypercaloric diet, with adequate quantities of protein and fiber but excessive amounts of simple carbohydrates and saturated fat and a low quantity of polyunsaturated fat. Those studies also showed that most of the children were sedentary [36,38].…”
Section: Discussionmentioning
confidence: 99%
“…Results from others studies [36][37][38] in urban locations of the same region showed that children consumed a hypercaloric diet, with adequate quantities of protein and fiber but excessive amounts of simple carbohydrates and saturated fat and a low quantity of polyunsaturated fat. Those studies also showed that most of the children were sedentary [36,38]. The development of obesity secondary to genetic or excessive consumption of food has been proposed as a risk factor for developing metabolic alterations including insulin resistance and diabetes mellitus [39].…”
Section: Discussionmentioning
confidence: 99%
“…24a That these findings are highly relevant to humans is indicated by situations in which dietary cholesterol and saturated fat feeding result in larger LDL particles. 25,26 The authors of these manuscripts focused on the potential increase in atherogenicity of small dense LDL. However, the likelihood that saturated fat-rich diet induces accumulation of larger, more cholesteryl ester-rich LDL, probably as a result of increased hepatic secretion of ACAT2-derived cholesteryl esters, seems more likely to indicate a state of increased, not decreased, atherogenicity, analogous to that repeatedly documented in studies in nonhuman primates.…”
Section: Cellular Functionmentioning
confidence: 99%
“…7,10,11 The relation between dietary and serum cholesterol is complicated by the large variability in individual response to dietary cholesterol. [11][12][13] Despite the fact that some studies have shown an association between egg consumption and CHD, 14 no previous study has examined whether egg consumption is associated with the risk of HF in a community setting.…”
mentioning
confidence: 99%